Recession hardships, personal control, and the amplification of psychological distress: Differential responses to cumulative stress exposure during the U.S. Great Recession. (April 2020) - Koltai, Jonathan; Stuckler, David
Abstract: Recessions pose risks to mental health, yet the psychosocial mechanisms involved are less clear. One critical factor may be people's perceived control when faced with multiple recession hardships. Here we test a structural amplification hypothesis by assessing the role of perceived control as a mediator and moderator of the relation between recession shocks and psychological distress. We draw on waves 2 (2004–2006) and 3 (2013–2014) of the Midlife in the United States study (MIDUS), covering 1, 739 US adults under age 75 from before and after the Great Recession. Our statistical models reveal that perceived control declines while distress rises in association with a greater accumulation of recession-related hardships. Perceived control partially mediated the recession hardships-distress association, attenuating it by about one-fifth. Further, perceived control modified the association between recession hardships and distress; individuals who reported larger declines in personal control had greater increases in distress, whereas those who experienced hardships but increased their perceived control did not exhibit significant changes in distress levels. Taken together, our findings support the structural amplification hypothesis, whereby an accumulation of recession hardships erode coping resources that would otherwise protect individuals from the mental health effects of stress exposure. Future research is needed to better understand sources of resilience at individual, community, and societal levels to help ameliorate sentiments of powerlessness and lack of perceived control during economic recessions. Highlights: Distress rises in association with the number of recession hardships people experience. Personal control declines in association with the number of recession hardships experienced. Hardships-distress association reduced by about 20% when including personal control in the model. The hardships-distress link was amplified for those who experienced declines control. Increases in control buffered the hardships distress association.